Clinical profile of Wilson disease in children between 1 and 12 years of age admitted at a tertiary care center - Sanikam, Hareesh; Bheeman, Basavaraj (Indian Journal of Child Health, 2019)
Background: Wilson disease (WD) is a rare autosomal recessive disorder characterized by the accumulation of copper in the liver, brain, cornea, and kidneys. Asymptomatic nature of disease at earlier stages leads to diagnostic enigma. Objective: The objective of this study was to study the clinical, biochemical, and histological profile of WD in children between 1 and 12 years of age. Methodology: It was a hospital-based descriptive study. All children between 1 and 12 years of age who were admitted with symptoms of liver disease and neuropsychiatric symptoms were screened for WD. Low serum ceruloplasmin (<20 mg/dl) and presence of Kayser–Fleischer rings in cornea were the parameters for diagnosis of WD in the study. Clinical and laboratory data were collected from 32 children diagnosed with WD. Evaluation included detailed history and physical examination, ultrasound abdomen, upper endoscopy, laboratory examination, and liver biopsy. Results: The mean age of presentation was 9.2 years. Hepatic manifestations (53%) were the main presentation followed by neurologic (25%) and hepatocerebral (18.7%) manifestations. Predominant symptom was jaundice in 64.7% of children with hepatic manifestations. Speech disturbance was found to be the most common symptom in neurologic presentation. Ultrasound abdomen showed features of portal hypertension in 11 (34.7%) children. Different grades of esophageal varices were noted in 13 (40.5%) children. Histopathology of biopsied samples showed evidence of cirrhosis in 18 (56.2%) children and features of chronic active hepatitis in 14 (43.7%) children. Conclusion: Diagnosis of WD in children is obscure and this may invariably decelerate the diagnosis and prognosis of this malady. Therefore, children presenting with any form of liver disease and/or neuropsychiatric features, WD must be suspected and further investigations should be carried out.